2019
DOI: 10.1055/a-0841-6638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin Supplementation On Blood Pressure: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Melatonin is a physiological indoleamine secreted from the pineal gland into the bloodstream. This hormone has antioxidant effects in cardiovascular disease, but the evidence regarding its effects on blood pressure (BP) has not been conclusive. Therefore, we assessed the impact of melatonin supplementation on systolic BP (SBP) and diastolic BP (DBP) through a systematic review and meta—analysis of available randomized controlled trials (RCTs). Medline, Scopus, Web of Science, Cochrane library, and Google schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Based on our results, melatonin treatment reduced blood pressure in the nicotine-related AAA model. As accumulating evidence has shown that melatonin affects blood pressure, a systematic review and meta-analysis, including five randomized controlled trials (RCTs), identified a significant reduction in systolic blood pressure and diastolic blood pressure after supplementation with melatonin, compared with a control treatment (Hadi et al, 2019). The proposed mechanisms underpinning melatonin's effects on blood pressure include: anti-inflammatory action via inhibition of the cyclooxygenase-2 (COX-2) enzyme, scavenging of free radicals, activation of antioxidant defense enzymes, an increase in nitric oxide (NO) production, and reduction of great artery resistance to blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, melatonin treatment reduced blood pressure in the nicotine-related AAA model. As accumulating evidence has shown that melatonin affects blood pressure, a systematic review and meta-analysis, including five randomized controlled trials (RCTs), identified a significant reduction in systolic blood pressure and diastolic blood pressure after supplementation with melatonin, compared with a control treatment (Hadi et al, 2019). The proposed mechanisms underpinning melatonin's effects on blood pressure include: anti-inflammatory action via inhibition of the cyclooxygenase-2 (COX-2) enzyme, scavenging of free radicals, activation of antioxidant defense enzymes, an increase in nitric oxide (NO) production, and reduction of great artery resistance to blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] Recently, developing new strategies including use of nutritional and bioactive compounds with antihypertensive medications is of high attention. [5,6] Momordica charantia L (MC) is a member of the Cucurbitaceae family. [7,8] The two most common names of M. charantia are bitter melon and bitter gourd.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Lifestyle modifications and pharmacological treatments are the leading suggestions to management and treatment of high BP. [8][9][10] Nevertheless, long-term pharmacological agents lead to different adverse side effects, and also compliance with lifestyle modifications is hard to be performed. [10,11] Thus, recognizing the alternative approaches, the same complementary agents with antihypertensive features have attracted a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Thus, recognizing the alternative approaches, the same complementary agents with antihypertensive features have attracted a lot of attention. [9] Recently, several evidences documented that gut microbiome dysbiosis has been related to high BP, and manipulation of the gut microbiota may lead to the improvement of new antihypertensive approaches. [12][13][14] Probiotics fermented milk (PFM) like yogurt and cultured soured milk as functional foods are the easiest and possible way for manipulation of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%